Bad kitty gets a bath - Bruel, Nick (Square Fish New York, 2009)
Takes a humorous look at the normal way cats bathe, why it is inappropriate for humans to bathe that way, and the challenges of trying to give a cat a real bath with soap and water. Includes fun facts, glossary, and other information